2004
DOI: 10.1074/jbc.m402762200
|View full text |Cite
|
Sign up to set email alerts
|

DiaA, a Novel DnaA-binding Protein, Ensures the Timely Initiation of Escherichia coli Chromosome Replication

Abstract: The DnaA protein is the initiator of Escherichia coli chromosomal replication. In this study, we identify a novel DnaA-associating protein, DiaA, that is required for the timely initiation of replication during the cell cycle. DiaA promotes the growth of specific temperature-sensitive dnaA mutants and ensures stable minichromosome maintenance, whereas DiaA does not decrease the cellular DnaA content. A diaA::Tn5 mutation suppresses the cold-sensitive growth of an overinitiation type dnaA mutant independently o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
191
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(201 citation statements)
references
References 52 publications
9
191
1
Order By: Relevance
“…Consequently, E. coli DiaA acts as a positive regulator of the initiation of DNA replication. In the absence of DiaA, initiation of DNA replication is delayed and in E. coli cells with two oriC copies, it only occurs from one of these, resulting in cells with three copies of their chromosome (14). In contrast, this is an extremely rare occurrence in wild-type E. coli cells.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Consequently, E. coli DiaA acts as a positive regulator of the initiation of DNA replication. In the absence of DiaA, initiation of DNA replication is delayed and in E. coli cells with two oriC copies, it only occurs from one of these, resulting in cells with three copies of their chromosome (14). In contrast, this is an extremely rare occurrence in wild-type E. coli cells.…”
mentioning
confidence: 78%
“…In E. coli, DiaA is necessary to ensure the timely initiation of DNA replication (14). DiaA forms a tetramer and binds to multiple molecules of DnaA, promoting (i) the binding of DnaA to the origin of replication in E. coli (known as oriC), (ii) ATP-DnaA-specific conformational changes in the oriC complex, and (iii) the unwinding of oriC DNA (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other experiments have suggested a role for the ATPase domain in oligomerization [6,7,15, 16,20]. Together, the observations that full-length DnaA from E.coli exists as a monomer in both the ADP-and ATP-bound forms, as well as in the presence of DNA that contains a single high affinity binding site [9,12], have made it difficult to characterize the exact nature of self-oligomerization.In addition to oligomerization, cross-linking studies have shown that the N-terminal domain of DnaA interacts directly with both DnaB [1] and the regulatory protein DiaA [21]. For DnaB, the regions of interaction were further defined by solid phase binding assays, which showed that residues 24-86 from the N-terminal domain, as well as residues in domain III, were important [20].…”
mentioning
confidence: 99%
“…In addition to oligomerization, cross-linking studies have shown that the N-terminal domain of DnaA interacts directly with both DnaB [1] and the regulatory protein DiaA [21]. For DnaB, the regions of interaction were further defined by solid phase binding assays, which showed that residues 24-86 from the N-terminal domain, as well as residues in domain III, were important [20].…”
mentioning
confidence: 99%